Efeito residual do lodo de esgoto e de manejos mecanizados na produção de tapetes e na extração de nutrientes pela grama esmeralda - Backes, Clarice; Santos, Alessandro José Marques; de Godoy, Leandro José Grava [UNESP]; Villas Bôas, Roberto Lyra [UNESP]; Ribon, Adriana Aparecida; de Bessa, Stephanie Vicente (My University, 2017)
The sewage sludge can be an alternative to minimize the cost with fertilizer in agriculture. The treatments were of five doses of sludge, another treatment with NPK and two management systems. There were residual effect of sludge application and also of chemical fertilization in the soil cover rate by sod. There was no residual effect of the use of surface chisel. The soil needs a replenishing of nutrients because, in a cycle without fertilization there were no nutrients in soil, being transported along with the zoysiagrass sod.
Residual effect of sewage sludge and mechanized management in the production of carpets and in the extraction of nutrients for zoysiagrass
Keywords: Fertilization; Soil compaction; Turf